2020
DOI: 10.2147/cmar.s258196
|View full text |Cite
|
Sign up to set email alerts
|

<p>Glucometabolic Reprogramming in the Hepatocellular Carcinoma Microenvironment: Cause and Effect</p>

Abstract: Hepatocellular carcinoma (HCC) is a tumor that exhibits glucometabolic reprogramming, with a high incidence and poor prognosis. Usually, HCC is not discovered until an advanced stage. Sorafenib is almost the only drug that is effective at treating advanced HCC, and promising metabolism-related therapeutic targets of HCC are urgently needed. The "Warburg effect" illustrates that tumor cells tend to choose aerobic glycolysis over oxidative phosphorylation (OXPHOS), which is closely related to the features of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 220 publications
(287 reference statements)
0
15
0
Order By: Relevance
“…Nevertheless, our data in hepatic cancer cell line Huh7 indicated that in transformed hepatic cells, rescuing miR-22-3p levels resulted in an increased glycolysis rate, as well as a decrease in mitochondrial respiration. This typically cancerous hallmark of reprogramming the cell metabolism to a more glycolytic phenotype could thus negatively impact the outcome of HCC patients, since this process provides metabolic adaptations suited for HCC progression (e.g., increased metabolites for lipid, amino acids, and nucleotide synthesis) [ 49 ]. Therefore, these findings should instruct future studies to be cautious regarding the development of a therapeutic approach involving miR-22-3p, as this miRNA presents a highly context-dependent versatility of its functions.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our data in hepatic cancer cell line Huh7 indicated that in transformed hepatic cells, rescuing miR-22-3p levels resulted in an increased glycolysis rate, as well as a decrease in mitochondrial respiration. This typically cancerous hallmark of reprogramming the cell metabolism to a more glycolytic phenotype could thus negatively impact the outcome of HCC patients, since this process provides metabolic adaptations suited for HCC progression (e.g., increased metabolites for lipid, amino acids, and nucleotide synthesis) [ 49 ]. Therefore, these findings should instruct future studies to be cautious regarding the development of a therapeutic approach involving miR-22-3p, as this miRNA presents a highly context-dependent versatility of its functions.…”
Section: Discussionmentioning
confidence: 99%
“…Although current HCC therapy is still far from optimal, the promising advances we are witnessing today undoubtedly come from an increased understanding of the fundamental aspects of hepatocarcinogenesis. Better knowledge of tumor cell metabolism [ 25 ], HCC epigenetics [ 26 ], HCC cancer stem cells [ 27 ] and the immunology of HCC, and the hepatic environment [ 28 ] will provide new avenues for improved therapeutic intervention. Moreover, further exploration of the role of the gut microbiome and the gut–liver axis in hepatocarcinogenesis will also deliver potential diagnostic tools and therapeutic targets [ 29 ].…”
mentioning
confidence: 99%
“…In fact, innate immune cells, as the other ‘weapon’ of defense in humans also serve important roles in the development of HCC ( 117 ). In fact, in addition to immune cells, hypoxia and glycolysis further promote the formation of the immunosuppressive tumor microenvironment and ultimately promote the metastasis and immune escape of HCC ( 118 , 119 ). However, how these metabolic factors exactly regulate various types of immune cells and whether they are regulated by immune cells in turn remains to be explored.…”
Section: Discussionmentioning
confidence: 99%